KONSTRUKSI DAN VALIDASI MODUL PEMBELAJARAN BIOLOGI BERBASIS KONSTRUKTIVISME DAN PROBLEM SOLVING UNTUK SISWA SMA KELAS XI IPA - Afsa, Rini; Haviz, M.; Rahmi, Elvy (Jurnal Pembelajaran MIPA, 2014)
The research was aimed to design and know about validation of biology module based on constructivisme and problem solving. The kind of this research was Research of Development. This research used 4-D model developing, they were define, design, develop and disseminate. Prosedure of research have been done in three phase, they are define, design and develop. Biology module based on constructivisme and problem solving was valid. Based on the result of validation and analysis quantitavely and qualitatively, module development was also based on characteristic of constructivisme and problem solving approach. So, the quality of development result product was valid based on result of validation that have done.Key words: develop, construction, validation, module, constructivisme, problem solving